INCIDENCE AND THERAPY OF RELAPSE AFTER ALLOGENEIC HEMATOPOIETIC STEM CELL TRANSPLANTATION - Lemajić, Nikola; Todorovic Balint, Milena; Peulic, Nikola (Srpski medicinski časopis Lekarske komore, 2022)
Introduction/Aim: Disease relapse after allogeneic hematopoietic stem cell transplantation (allo-HSCT) is one of the most common and most severe post transplantation complications and represents the leading cause of treatment failure and patient death. The aim of this study is to assess the frequency and types of relapse, in relation to the time of occurrence; analyze the influence of conditioning regimens on relapse occurrence; review the therapeutic options after the occurrence of relapse; assess the prognosis in patients with relapse.Methods: This retrospective cohort study included 58 patients who underwent allogeneic hematopoietic stem cell transplantation (allo-HSCT). Pre-transplantation therapy was performed with a reduced-intensity conditioning regimen (RIC) or a myeloablative regimen (MAC). The diagnosis of relapse was made through myelogram analysis, analysis of cytogenetics, analysis of minimal residual disease (MRD), analysis of cellular chimerism, and analysis of immunohematological chimerism of blood group antigens. A database was formed in relation to the examined patient characteristics. Patient survival was analyzed using the Kaplan-Meier method and the log-rang test.Results: MAC (43 patients) was used more frequently than RIC (15 patients), as a conditioning regimen. After transplantation, 18 (34%) out of 53 patients had a relapse. The choice of regimen did not affect the occurrence of relapse, but patients on the RIC regimen lived longer (38.5 ± 7 months) as compared to patients on the MAC regimen (27.8 ± 3.5 months). However, the difference in survival was without statistical significance (p = 0.318). The median survival time of patients who relapsed was 26 ± 5 months, while patients without disease relapse had a median survival time of 41 ± 4 months.Conclusion: Patients who received reduced-intensity regimens (RIC) had a longer survival time, without an increase in the relapse rate. In future, consideration should be given to the inclusion of patients older than 60 years, as candidates for transplantation, as well as to the possible use of prophylactic therapy aimed at preventing relapse in high-risk patients.
Keywords: reduced intensity conditioning; myeloablative conditioning; survival